Impact of age on the selection of nuclear cardiology stress protocols: The INCAPS (IAEA nuclear cardiology protocols) study. (15th May 2018) - Al-Mallah, Mouaz H.; Pascual, Thomas N.B.; Mercuri, Mathew; Vitola, João V.; Karthikeyan, Ganesan; Better, Nathan; Dondi, Maurizio; Paez, Diana; Einstein, Andrew J.; ,
Abstract: Background: There is growing concern about radiation exposure from nuclear myocardial perfusion imaging (MPI), particularly among younger patients who are more prone to develop untoward effects of ionizing radiation, and hence US and European professional society guidelines recommend age as a consideration in weighing radiation risk from MPI. We aimed to determine how patient radiation doses from MPI vary across age groups in a large contemporary international cohort. Methods: Data were collected as part of a global cross-sectional study of centers performing MPI coordinated by the International Atomic Energy Agency (IAEA). Sites provided information on each MPI study completed during a single week in March–April 2013. We compared across age groups laboratory adherence to pre-specified radiation-related best practices, radiation effective dose (ED; a whole-body measure reflecting the amount of radiation to each organ and its relative sensitivity to radiation's deleterious effects), and the proportion of patients with ED ≤ 9 mSv, a target level specified in guidelines. Results: Among 7911 patients undergoing MPI in 308 laboratories in 65 countries, mean ED was 10.0 ± 4.5 mSv with slightly higher exposure among younger age groups (trend p value < 0.001). There was no difference in the proportion of patients with ED ≤ 9 mSv across age groups, or in adherence to best practices based on the median age of patients in a laboratory. Conclusions: In contemporary nuclear cardiology practice, the age of the patient appears not to impact protocol selection and radiation dose, contrary to professional society guidelines.